United States Army logistics from the American Revolution to 9/11 - Waddell, Steve R. (PSI reports (Westport, CT), 2010)
You can train men to fight. You can plan for the invasion. But you can't have success on the battlefield if you cannot move the men and material into position. Success is not possible without logistical support and capabilities. The U.S. Army's logistics system began with practically nothing and through numerous conflicts and periods of peace has developed into a first rate supply system capable of supporting the global military commitments of the present day. This work presents the history of U.S. Army logistics as one of evolution, trial and error, and occasionally revolutionary change over a period of two hundred plus years. It is important that logisticians and combat leaders alike understand how the United States Army logistical system developed; the challenges that had to be overcome; and the successes and failures encountered along the way. Creating the U.S. Army in 1775 proved to be easy compared to the task of keeping the army adequately supplied over the short and long term. The availability of resources, industrial capacity, size of the army, geographic scope of operations, organization of the logistics system, competent leadership, congressional support, funding, and new technology have, and continue to impact the logistical system on a daily basis. Each new period of peace or war has brought new challenges and requirements. This work is broken into two key parts. First, to inform the reader on the basic history of U.S. Army Logistics. Second, to identify the key factors that influenced the development of the logistical system.